Entrepreneurship vs. wealth generation - Rincón Angarita, Jorge Francisco (Universidad Francisco de Paula Santander, 2014)
This article discusses reflection entrepreneurship in Colombia as an element that generates wealth. The subject is approached from a national level, leading us to review is being done in the country in terms of investment in the creation of alternatives for the creation of new businesses, the legalization of the informal sector and employment generation. All within a project to determine whether entrepreneurship is a solution for the acquisition of resources to the sustainability of new entrepreneurs and continuity of legally constituted business framework. 1 World, 2 National, Regional 3, and 4 Local: Inside the document refers to four kinds of analysis done. Finding and documentation leading us to reflect on all areas pertaining to the particular issue; finding significant figures allow us to see firsthand how the subject behaves entrepreneurship globally and to discuss the creation of wealth. All this innovation-oriented, because the latter is called upon to define the basic characteristics of the new companies that guide their actions to raise their mission objectives differentiators that contribute to competitiveness.